Macroeconomic Analysis and Financial Ratios on Sharia Commercial Bank Profitability: A Case Study of Indonesia - Faiza Husnayeni Nahar; Calvin Faza; Muhammad Azizurrohman (Universitas Ahmad Dahlan, 2020)
Having experienced significant growth, sharia commercial bank in Indonesia has become one of the drivers of economic growth in Indonesia. This study aims to analyze the effect of macroeconomic and financial ratios on the profitability of Islamic commercial banks in Indonesia. This study used qualitative data using secondary data during the period 2011-2018. The methodology used is panel data which combines time series data and cross section data. Variables used include Non Performing Finance (NPF), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (OER), Inflation, Domestic Product Growth (GDP), and Exchange Rates. The results of this study indicate that Non-Performing Finance (NPF), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (OER) have a significant influence on Islamic Bank Return On Assets (ROA) in Indonesia. Meanwhile, Growth Domestic Product (GDP), and Exchange Rate appear with no significant effect on the Return on Assets (ROA) of Sharia Commercial Banks in Indonesia.